Kontribusi Perbankan Syariah dalam Pengembangan Usaha Ekonomi Mikro di Bima - Jairin Jairin (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2019)
Changes in the level of life of the people in Bima are influenced by various levels of media, making a shift to the level and lifestyle of the Bima Community, ranging from economic development procedures to trust competition on the performance of both Sharia Bank performance and confessional banking performance. In the modern era all lines of information were found by the Bima community, and then elaborated on the strategic issues of education in the international and national arena. The problem of the low quality of our education does not escape the attention of this article. In the next section, this article raises the development of Islamic economics, and influancing the development of Islamic banking to improve the economy of the community in the modern Bima in this era. The assumption underlying this article is the modeen era has implications for the need for education and economic reform in Bima. The goal is that education has the ability to accommodate, anticipate, and respond to challenges and changes that are and will occur. Conversely, if no renewal is carried out, then education in Indonesia will be left behind by the rhythm of change.